MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MEDIA AUDIO PADA MATA PELAJARAN PPKn DI KELAS VIII SMP NEGERI 1 TIGAPANAH TAHUN PELAJARAN 2018/2019 - Karo, Karmila Br (Jurnal Ilmiah Aquinas, 2020)
The kind of this research is classroom action research utilizing audio in PPKn. The aim in this research are to describe the mastery of student learning and student learning outcomes utilizing audio media in PPKn at SMP Negeri 1 Tigapanah in the second semester of academic year of 2018/2019. This classroom action research consists of two cycles, consists of phases: planning, implementation, evaluating and reflection. First cycle utilizing audio, second cycle utilizing audio media too. The subject of this research uses one class as research sample, all students of grade VIII in the second semester of academic year of 2018/2019 which amounted to 20 student.            First cycle implementation, data obtained that amount of students who completed individually are 15 student and not completed individually are 5 student, while students complete classically is 75% and students not complete classically is 25%, and the average value is 60,1 %. Second cycle implementation, data obtained that amount of students who completed individually are 18 student and not completed individually are 2 student, while students complete classically is 90% and students not complete classically is 5%, and the average value is 77,4 %.Based on the results of data analysis, it can be concluded that the implementation of learning using audio media has been categorized as good, mastery learning is achieved and student learning outcomes increase in PPKn subjects in class VIII SMP Negeri 1 Tigapanah Tahun Pelajaran 2018/2019learning outcomes,  utilizing audio media